2020
DOI: 10.1093/noajnl/vdaa051
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibition as a therapeutic approach in atypical teratoid/rhabdoid tumors

Abstract: Background Atypical teratoid/thabdoid tumor (AT/RT) remains a difficult-to-treat tumor with a 5-year overall survival rate of 15%–45%. Proteasome inhibition has recently been opened as an avenue for cancer treatment with the FDA approval of bortezomib (BTZ) in 2003 and carfilzomib (CFZ) in 2012. The aim of this study was to identify and characterize a pre-approved targeted therapy with potential for clinical trials in AT/RT. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…An unbiased drug screen of AT/RT identified proteasome inhibitors as being highly effective in vitro. The brain-penetrant proteasome inhibitor marizomib demonstrated activity against BT16 and MAF-737A AT/RT orthotopic xenografts [65] . Clinical development of marizomib is currently halted, however, the orally bioavailable and brain-penetrant proteasome inhibitor ixazomib also demonstrated activity against malignant rhabdoid tumor (MRT) in vitro and in vivo and killed AT/RT cells [63] .…”
Section: Discussionmentioning
confidence: 99%
“…An unbiased drug screen of AT/RT identified proteasome inhibitors as being highly effective in vitro. The brain-penetrant proteasome inhibitor marizomib demonstrated activity against BT16 and MAF-737A AT/RT orthotopic xenografts [65] . Clinical development of marizomib is currently halted, however, the orally bioavailable and brain-penetrant proteasome inhibitor ixazomib also demonstrated activity against malignant rhabdoid tumor (MRT) in vitro and in vivo and killed AT/RT cells [63] .…”
Section: Discussionmentioning
confidence: 99%
“…Kai et al studied high-dose chemotherapy with SCT and found that it may contribute to a better outcome [27]. Proteasome inhibitors (Marizomib, carfilzomib, and bortezomib) were recently studied as potential targeted therapy for patients with AT/RT, and tumor models have shown promising results [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Although cisplatin-or carboplatin-based chemotherapy regimens have been used in many centers [4], we did not yet have a standardized chemotherapy protocol for AT/RT in Taiwan during the study period. The recent discovery of the preclinical activity of proteasome inhibitors in AT/RT [40,41], however, has encouraged us to initiate a multi-center phase II trial using a proteasome inhibitor as an add-on therapy to standard chemotherapy for newly diagnosed AT/RT. Thirdly, since AT/RT is a rare cancer and the number of cases is limited, the analysis of the relationship between tumor site, treatment type, and age group required that small groups (of less than five patients) be combined as a single unit.…”
Section: Discussionmentioning
confidence: 99%
“…Another group had similar findings, showing that proteasomal inhibition paired with genetic suppression of autophagy led to durable responses in a faithful rhabdoid tumor mouse model [ 157 ]. These effects of proteasomal inhibition were similarly validated within the context of rhabdoid tumors, yet the synergistic effects when paired with autophagy inhibition were not observed in the context of ATRT [ 158 ]. Further studies are still needed to elucidate the clinical benefits of proteasomal inhibition in SMARCB1-deficient cancers.…”
Section: Therapeutic Vulnerabilities Of Smarcb1-deficient Cancersmentioning
confidence: 99%